Study of the Flexural Resistance of Unsaturated Polyester Composite Reinforced by Finely Ground Sugarcane Bagasse Fiber for Light Construction - Nusyirwan; Zulfadly Koto; Xhycho Vachanidyo (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
One of the polymer materials widely used in the field of engineering construction to be a candidate to replace metal materials is unsaturated polyester. This reason is because this material has many advantages such as low mass, ease of shape and resistance to moisture. However, this material still has many shortcomings, including low mechanical strength and easy cracking. Unsaturated polyester polymer material is widely used as a matrix for making composite materials for engineering fields such as vehicles and ship hulls. This research studies the flexural strength of composite materials from unsaturated polyester reinforced with finely ground sugarcane fibre. From the results of flexural strength testing, it is known that there is a tendency towards the variable addition of finely ground sugarcane fibre. increases from 10% to 20%, and after 20% the bending stress value tends to decrease. The maximum flexural stress value was obtained by adding a percentage of finely ground sugarcane fibre. with a percentage of 20% 102.32 MPa, this value can increase the maximum flexural stress value of pure polyester by 42.52 MPa, showing an increase of 249.63%